2012
DOI: 10.1371/journal.pone.0030590
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Induces Cell Death in Esophageal Cancer Cells through Modulating Notch Signaling

Abstract: BackgroundCurcumin inhibits the growth of esophageal cancer cell lines; however, the mechanism of action is not well understood. It is becoming increasingly clear that aberrant activation of Notch signaling has been associated with the development of esophageal cancer. Here, we have determined that curcumin inhibits esophageal cancer growth via a mechanism mediated through the Notch signaling pathway.Methodology/Principal FindingsIn this study, we show that curcumin treatment resulted in a dose and time depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
145
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(155 citation statements)
references
References 52 publications
(69 reference statements)
8
145
0
2
Order By: Relevance
“…In these reports, MMPs, the nuclear factor-kB pathway and micro-RNAs were reported to be associated with increases in invasive phenotypes. 46,47 Our data support these previous findings and we conclude that Notch1 has a role in a certain type of OSCC invasion. However, we need further investigation to determine what mechanisms underlie the invasiveness of OSCC cells because Notch signaling shows cross-talk with many other pathways and regulates the properties of these pathways based on complicated mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…In these reports, MMPs, the nuclear factor-kB pathway and micro-RNAs were reported to be associated with increases in invasive phenotypes. 46,47 Our data support these previous findings and we conclude that Notch1 has a role in a certain type of OSCC invasion. However, we need further investigation to determine what mechanisms underlie the invasiveness of OSCC cells because Notch signaling shows cross-talk with many other pathways and regulates the properties of these pathways based on complicated mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, it seems that the effect of curcumin on T47D breast cancer cell line is time-and dose-dependent. Other studies shows that curcumin has inhibitory effect in the cells growth on the various types of cancer cell lines usually with a timedependent manner (Syng-Ai et al, 2004;Chakravarti et al, 2010;Watson et al, 2010;Subramaniam et al, 2012). Curcumin exerts its anticancer effect on different cellular factors (Sa and Das, 2008;Wilken, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin was found to induce miR-203 transcription in bladder cancer cells that leads to downregulation of miR-203 target genes Akt2 and Src, culminating in decreased cell proliferation and increased apoptosis (Saini et al, 2011). Upregulation of the tumor suppressor let-7a miRNA is associated with curcumin-induced apoptosis in esophageal cancer cells (Subramaniam et al, 2012). Our present data revealed that curcumin treatment resulted in a dose-dependent and significant elevation of miR-9 expression in SKOV3 ovarian cancer cells, compared to untreated control cells.…”
Section: Discussionmentioning
confidence: 99%